2019
DOI: 10.1590/s1517-707620190003.0735
|View full text |Cite
|
Sign up to set email alerts
|

Wood basic density effect of Eucalyptus grandis in the paper making

Abstract: The basic density is the main technical property of the wood due to the fact of the easy determination and correlation with the others wood properties. In this article, it was evaluated wood chips from a five-years-old Eucalyptus grandis in three different silvicultural treatments for pulp and paper production. First, a conventional kraft pulping was executed in the same conditions and then submitted to some elemental chlorine free (ECF) bleaching process to achieve the target brightness of 88 ± 1% ISO. The bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Cremonez [37] and Magaton [38] presented values of SWC for Eucalyptus grandis and Eucalyptus urophylla between 3.6 and 4.6 m 3 wood /ton pulp , which are tendentially higher than the values observed here with the exception of that of A. longifolia.…”
Section: Fiber Propertiescontrasting
confidence: 74%
“…Cremonez [37] and Magaton [38] presented values of SWC for Eucalyptus grandis and Eucalyptus urophylla between 3.6 and 4.6 m 3 wood /ton pulp , which are tendentially higher than the values observed here with the exception of that of A. longifolia.…”
Section: Fiber Propertiescontrasting
confidence: 74%
“…VIEIRA, W.L. et al Corymbia citriodora wood for pulp and paper Studying the effect of E. grandis wood density on papermaking, Cremonez et al (2019) concluded that increase in wood density did not promote variations in pulp yield, considering the same cooking conditions. However, denser wood had lower specific consumption, making it difficult to ignite and, hence, impairing selectivity of the pulping process.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus urophylla had the highest wood basic density, with a mean value of 440.2 kg/m 3 . Previously, Cremonez et al (2019) reported that wood density ranged from 381 kg/m 3 to 436 kg/m 3 for eucalyptus tree species. da Silva et al ( 2017) found that hybrid urograndis had an average tree basic density of 400 kg/m 3 at 34 months and 420 kg/m 3 at 62 months old.…”
Section: Wood Basic Density Distributionmentioning
confidence: 99%